Psycholinguistic Paradigm of the Medical Staff – Patients Communicative Interaction in the Conditions of COVID-19 in Ukraine and Scotland - Наталія Михальчук; Валерій Зливков; Світлана Лукомська; Олександр Набочук; Ніна Христич (Психолінгвістика, 2022)
Purpose. The purpose of this research is, based on the results of our empirical research, to determine the psycholinguistic paradigms of the Medical staff – Patients communicative interaction in the conditions of COVID-19 in Ukraine and Scotland, in particular in the context of the perception of the emotional concepts by respondents.